Electrolyte containing multiple cations, aqueous zinc ion battery and preparation method
By using multiple cationic electrolytes in acid zinc-manganese dioxide batteries, a bimetallic active site and a self-sustaining acidic environment is formed, and the problem of poor stability of zinc anode in high acidic media is solved, which significantly improves the cycle life of the battery and Capacity stability.
Patent Information
- Application Number
- CN202411576155.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The zinc anode of acidic zinc-manganese dioxide batteries has poor stability in highly acidic media, which is prone to corrosion and hydrogen evolution reactions, resulting in rapid capacity degradation and unstable electrode surfaces.
Using an electrolyte containing multiple cations, including zinc salt, manganese salt, copper salt and indium salt, the formation of bimetallic active site In-CuZn5 on the surface of the zinc anode, the hydrogen evolution reaction is inhibited, and SnO2 is generated through in situ hydrolysis of Sn4+ to form SnO2. Self-sustaining an acidic environment to enhance the stability of the zinc anode.
It significantly inhibits the adverse side reactions of the zinc anode, improves the stability of the zinc anode in an acidic environment, extends the cycle life and capacity stability of the battery, and achieves a cycle life of up to 2,250 hours in a high current density environment.
Smart Images

Figure CN119447511A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of zinc ion batteries, and specifically relates to an electrolyte containing multiple cations, an aqueous zinc ion battery, and a preparation method. Background Art
[0002] Acid zinc-manganese dioxide batteries have high safety, environmental protection and affordability, and have important application potential in large-scale energy storage systems. Energy storage systems utilize the high H + Driven MnO2 / Mn 2+ The conversion mechanism can achieve a higher discharge voltage (~2.0V vs. Zn 2+ / Zn) and theoretical capacity (616 mAh g -1 ).
[0003] However, in highly acidic media, zinc anodes face major challenges, such as severe corrosion and hydrogen evolution reaction (HER), which are important causes of rapid capacity degradation and electrode surface instability. Therefore, acidic zinc-manganese dioxide batteries have limited performance at high currents (≥5 mA cm -2 ) and large capacity (≥5mA cm -2 ) are facing great dangers when working under acidic conditions. In addition, manganese dioxide cathode materials also have problems such as slow kinetics, uneven deposition and active material shedding, resulting in low reversible capacity and poor cyclability. Therefore, solving the stability of zinc anode in acidic media, especially by inhibiting adverse side reactions, is crucial to improving battery reliability and performance. Summary of the invention
[0004] The purpose of the present application is to provide an electrolyte containing multiple cations, an aqueous zinc ion battery and a preparation method, so as to solve the technical problems existing in the prior art that the zinc anode of the acidic zinc-manganese dioxide battery has poor stability in a highly acidic medium, is prone to adverse side reactions, and leads to rapid degradation of the battery capacity and instability of the electrode surface.
[0005] In order to achieve the above objectives, the present application provides, in a first aspect, an electrolyte containing multiple cations, including a solvent and an electrolyte dissolved in the solvent, wherein the electrolyte includes a zinc salt, a manganese salt, a copper salt and an indium salt.
[0006] In one or more embodiments, the molar concentration of the zinc salt is 1.8 to 2.2 mol / L, and the molar concentration of the manganese salt is 0.18 to 0.22 mol / L.
[0007] In one or more embodiments, the zinc salt is ZnSO4 and the manganese salt is MnSO4.
[0008] In one or more embodiments, the molar concentration of the copper salt is 45 to 55 mmol / L, and the molar concentration of the indium salt is 45 to 55 mmol / L.
[0009] In one or more embodiments, the copper salt is CuCl2 and the indium salt is InCl3.
[0010] In one or more embodiments, the electrolyte further includes a tin salt.
[0011] In one or more embodiments, the molar concentration of the tin salt is 45 to 55 mmol / L.
[0012] In one or more embodiments, the tin salt is SnCl4.
[0013] In one or more embodiments, the solvent is water.
[0014] A second aspect of the present application provides an application of the electrolyte described in any of the above embodiments in the preparation of an aqueous zinc ion battery.
[0015] A third aspect of the present application provides an aqueous zinc ion battery, comprising a positive electrode, a negative electrode, a separator and the electrolyte described in any of the above embodiments.
[0016] In one or more embodiments, the positive electrode is a manganese dioxide positive electrode, and the negative electrode is a metal zinc negative electrode.
[0017] In one or more embodiments, the separator is a glass fiber membrane or a cellulose membrane.
[0018] The fourth aspect of the present application provides a method for preparing an aqueous zinc ion battery, comprising:
[0019] Dissolve KMnO4 and fully react with MnSO4, collect the precipitate, wash and dry it to obtain MnO2 positive electrode material;
[0020] After mixing the MnO2 positive electrode material, the conductive additive and polyvinylidene fluoride, N-methylpyrrolidone is added and stirred to obtain a positive electrode slurry;
[0021] The positive electrode slurry is coated on the hydrophilic carbon paper, and the loading amount of the MnO2 positive electrode material is 1.5-3 mg / cm 2 , after drying, a manganese dioxide positive electrode is obtained;
[0022] The manganese dioxide positive electrode, the metal zinc negative electrode, the separator and the electrolyte according to any one of claims 1 to 6 are assembled to obtain an aqueous zinc ion battery.
[0023] Different from the prior art, the beneficial effects of this application are:
[0024] The electrolyte of the present application includes In 3+ , Cu 2+ Sn 4+ , Cu 2+ andIn 2+ It can form bimetallic active sites In-CuZn5 on the surface of zinc anode, provide abundant nucleation sites, promote efficient deposition of Zn, and effectively inhibit hydrogen evolution reaction, thereby improving the stability of zinc anode in acidic environment. 4+ It can hydrolyze in situ to generate SnO2 and HCl, establishing a self-sustaining acidic environment that is critical to aqueous zinc-ion batteries without the need for additional acidic media. SnO2 is highly acid-resistant and can greatly enhance the stability of zinc in acidic media, thereby improving the cycle life and capacity stability of the battery. When applied to zinc / zinc symmetrical batteries, it can 2 Achieve an amazing cycle life of up to 2250 hours under high current density environment;
[0025] This application adopts an innovative electrolyte decoupling strategy by adding In 3+ , Cu 2+ Sn 4+ , improving battery performance and life in challenging electrochemical environments, aiding the development of next-generation energy storage systems;
[0026] The aqueous zinc ion battery of the present invention has excellent cycle life and capacity stability. 2 After 200 cycles under the conditions of , it still maintained 84.9% of the initial capacity, far exceeding the aqueous zinc-ion battery using conventional electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 This is an image of the electrolyte of Effect Example 1 of the present application;
[0029] Figure 2 is a characterization diagram of the suspended matter in the electrolyte of Example 2 of the present application, wherein b is an XRD diffraction spectrum and c is a SEM image;
[0030] Figure 3 is the XRD diffraction spectrum of the zinc negative electrode of the zinc ion battery of Example 3 of the present application;
[0031] Figure 4 3 is a characterization diagram of the zinc negative electrode of the zinc ion battery of Example 3 of the present application, wherein e is a surface SEM image of the zinc negative electrode, and f is a cross-sectional SEM image of the zinc negative electrode;
[0032] Figure 5 is the Tafel plot of In-Cu@Zn and Bare Zn;
[0033] Figure 6 is the linear sweep voltammetry curve of In-Cu@Zn and Bare Zn;
[0034] Figure 7 It is the HER Gibbs free energy data diagram of In-CuZn5 and Zn(101);
[0035] Figure 8 The zinc / zinc symmetrical battery with different electrolytes in Example 4 of the present application is 2 -5mAh / cm 2 The charge and discharge performance data diagram below;
[0036] Fig. 9 The zinc / zinc symmetrical battery using different electrolytes in Example 4 of the present application is 2 -10mAh cm 2 The charge and discharge performance data diagram below;
[0037] Fig.10 This is a graph of the cycle performance test data of Effect Example 5 of the present application. DETAILED DESCRIPTION
[0038] In order to enable those skilled in the art to better understand the technical solutions in the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present application.
[0039] Currently, the zinc anode of acidic zinc-manganese dioxide batteries is prone to severe corrosion and hydrogen evolution reaction (HER) in highly acidic media. These side reactions lead to rapid capacity degradation and unstable electrode surface.
[0040] In order to solve the above problems, the applicant introduced an innovative electrolyte decoupling strategy, which can significantly inhibit the occurrence of the above-mentioned adverse side reactions by adding multiple cations to conventional electrolytes, greatly enhance the stability of the zinc anode in an acidic environment, thereby improving the cycle life and capacity stability of the battery, and improving the performance and life of the battery in challenging electrochemical environments, which is conducive to the development of the next generation of energy storage systems.
[0041] Specifically, the present application provides an electrolyte containing multiple cations, wherein the electrolyte includes a solvent and an electrolyte, wherein the electrolyte includes a zinc salt, a manganese salt, a copper salt and an indium salt.
[0042] In one embodiment, the molar concentration of the zinc salt may be 1.8 to 2.2 mol / L, and the molar concentration of the manganese salt may be 0.18 to 0.22 mol / L.
[0043] In one embodiment, the molar concentration of the copper salt may be 45 to 55 mmol / L, and the molar concentration of the indium salt may be 45 to 55 mmol / L.
[0044] In one embodiment, the solvent may be water, and in particular, may be deionized water.
[0045] In one embodiment, the zinc salt may be ZnSO4, the manganese salt may be MnSO4, the copper salt may be CuCl2, and the indium salt may be InCl3.
[0046] In other embodiments, zinc salts, manganese salts, copper salts and indium salts may also be any soluble salts that can be formed by corresponding metal cations, for example, zinc salts may also be zinc chloride, etc., as long as the electrolyte has a suitable acidic pH value, generally around 3 to 4, which can achieve the effect of this embodiment.
[0047] Compared with the electrolyte of the conventional acidic aqueous zinc-manganese battery, the electrolyte of this embodiment has Cu 2+ andIn 3+ When the electrolyte is applied to aqueous zinc ion batteries, Cu 2+ andIn 3+ Bimetallic active sites In-CuZn5 can be spontaneously formed on the surface of zinc anode. The bimetallic active sites can provide abundant nucleation sites, thereby promoting the efficient deposition of Zn, while effectively inhibiting the hydrogen evolution reaction, thereby improving the stability of zinc anode in acidic environment.
[0048] In another embodiment, the electrolyte of the present application may further include tin salt, wherein the molar concentration of the tin salt may be 45 to 55 mmol / L.
[0049] The electrolyte solution of this embodiment further contains Sn as compared to the electrolyte solution of the above embodiment.4+ When applied in aqueous zinc-ion batteries, Sn 4+ It can be hydrolyzed in situ to generate SnO2, which is highly acid-resistant, so the SnO2 layer can greatly enhance the stability of zinc in acidic media.
[0050] In one embodiment, the tin salt may be SnCl4, which may also generate HCl upon in-situ hydrolysis, thereby establishing a self-sustaining acidic environment critical to aqueous zinc-ion batteries without the need for an additional acidic medium.
[0051] The electrolytes based on the above-mentioned embodiments, when applied to aqueous zinc ion batteries, can significantly inhibit the occurrence of adverse side reactions of the zinc anode, greatly enhance the stability of the zinc anode in acidic media, and thus improve the cycle life and capacity stability of the battery.
[0052] The present application also provides an aqueous zinc ion battery, which includes a positive electrode, a negative electrode, a separator and an electrolyte of any of the above embodiments.
[0053] Specifically, in one embodiment, the aqueous zinc ion battery may be a zinc-manganese battery, the corresponding positive electrode may be a manganese dioxide positive electrode, and the negative electrode may be a metallic zinc negative electrode.
[0054] In one embodiment, the separator may be a glass fiber membrane or a cellulose membrane.
[0055] In other embodiments, the aqueous zinc ion battery may also be other types of zinc ion batteries, such as a zinc / zinc symmetrical battery, in which case the positive electrode may be Zn 2+ The negative electrode can be a metal zinc negative electrode, which can also achieve the effect of this embodiment.
[0056] In one embodiment, the aqueous zinc ion battery can be a pouch battery. In other embodiments, it can be other types of batteries, such as dry batteries, etc., all of which can achieve the effects of this embodiment.
[0057] The present application also provides a method for preparing an aqueous zinc ion battery, comprising:
[0058] S100, dissolving KMnO4 and reacting it with MnSO4, collecting the precipitate, washing and drying it to obtain the MnO2 positive electrode material;
[0059] S200, mixing MnO2 positive electrode material, conductive additive and polyvinylidene fluoride, adding N-methylpyrrolidone and stirring to obtain positive electrode slurry;
[0060] In one embodiment, the conductive additive may be conductive carbon black Super P. In other embodiments, other conductive additives may also be used.
[0061] In one embodiment, the mass ratio of MnO2 positive electrode material, conductive additive and polyvinylidene fluoride can be 7:1:2; in other embodiments, the ratio can also be adjusted based on actual needs, and the effect of this embodiment can be achieved.
[0062] S300, the positive electrode slurry is coated on the hydrophilic carbon paper, and the loading amount of MnO2 positive electrode material is 1.5-3 mg / cm 2 , after drying, a manganese dioxide positive electrode is obtained;
[0063] S400, assembling a manganese dioxide positive electrode, a metal zinc negative electrode, a separator and an electrolyte according to any of the above embodiments to obtain an aqueous zinc ion battery.
[0064] The beneficial effects of the technical solution of the present application are further elaborated in detail below in conjunction with specific embodiments.
[0065] Embodiment 1:
[0066] An electrolyte containing multiple cations is prepared by the following steps:
[0067] 50 mM CuCl2 and 50 mM InCl3 were introduced into an aqueous electrolyte containing 2 M ZnSO4 and 0.2 M MnSO4, respectively, and a uniform electrolyte was formed after ultrasonic stirring for 20 min. The pH value of the electrolyte was 3.3.
[0068] Embodiment 2:
[0069] An electrolyte containing multiple cations is prepared by the following steps:
[0070] 50 mM CuCl2, 50 mM InCl3, and 50 mM SnCl4 were introduced into an aqueous electrolyte containing 2 M ZnSO4 and 0.2 M MnSO4, respectively, and a uniform electrolyte was formed after ultrasonic stirring for 20 min. The pH value of the electrolyte was 1.2.
[0071] Embodiment 3:
[0072] An aqueous zinc ion battery is prepared by the following steps:
[0073] (1) Weigh 0.8 g of KMnO4 and dissolve it in 80 ml of deionized water, stir it at room temperature for 30 minutes to completely dissolve it; then add 2.7 g of MnSO4·H2O and stir it for 30 minutes to produce a dark brown precipitate; transfer the mixed solution to a 100 ml polytetrafluoroethylene reaction flask, react at 180°C for 6 hours, cool to room temperature, collect the dark brown precipitate, wash it three times with deionized water and ethanol, and finally dry it in an oven at 60°C for 12 hours to obtain MnO2 positive electrode material powder;
[0074] (2) polyvinylidene fluoride (PVDF), Super P and the MnO2 positive electrode material powder of step (1) are mixed in a mass ratio of 1:2:7, N-methylpyrrolidone is added and stirred for 12 hours to obtain a positive electrode slurry, the positive electrode slurry is coated on a hydrophilic carbon paper, the loading amount of the active material (MnO2) is 2 mg / cm, and then the hydrophilic carbon paper is dried in a vacuum oven at 80°C overnight to obtain a manganese dioxide positive electrode;
[0075] (3) Assembly of zinc-manganese battery:
[0076] The manganese dioxide positive electrode, zinc foil and glass fiber prepared in step (2) were used as the positive electrode, negative electrode and separator respectively, and the electrolyte prepared in Example 1 was used as the electrolyte to assemble into a pouch battery with an area of 25 square centimeters.
[0077] Embodiment 4:
[0078] An aqueous zinc ion battery, the preparation method of which is basically the same as that of Example 3, except that: this embodiment uses the electrolyte prepared in Example 2 as the electrolyte.
[0079] Comparative Example 1:
[0080] An aqueous zinc ion battery, the preparation method is basically the same as that of Example 3, except that: the electrolyte of this comparative example is an aqueous electrolyte (pH 1.21) including 2M ZnSO4 and 0.2M MnSO4.
[0081] Effect Example 1: Characterization Analysis
[0082] The images of the electrolyte (In-Cu) of Example 1 and the electrolyte (In-Cu-Sn) of Example 2 were collected, and an aqueous electrolyte (BE, pH 4.5) including only 2M ZnSO4 and 0.2M MnSO4, and an aqueous electrolyte (In, pH 3.3) including 50mM InCl3, 2M ZnSO4 and 0.2M MnSO4 were introduced to obtain Figure 1 , Figure 1 This is an image of the electrolyte solution of Effect Example 1 of the present application.
[0083] like Figure 1 As shown, the electrolyte of Example 2 has higher turbidity and a large amount of suspended matter compared to other electrolytes.
[0084] In order to verify the specific composition of the suspended matter, XRD diffraction analysis and electron microscopy analysis were performed on the suspended matter. Figure 2 , Figure 2 It is a characterization diagram of the suspended matter in the electrolyte of Example 2 of the present application, wherein b is the XRD diffraction spectrum and c is the SEM image.
[0085] like Figure 2 As shown in b, the XRD diffraction spectrum of the suspension matches PDF No. 01-0625, which confirms that the suspension is SnO2. Figure 2 As shown in c, the suspended matter is granular and has a particle size less than 1 μm.
[0086] From the above experiments, it can be seen that in the electrolyte of Example 2, Sn 4+ SnO2 is generated by in-situ hydrolysis. Since SnO2 is highly acid-resistant, when the electrolyte is used in aqueous zinc-ion batteries, SnO2 can adhere to the surface of the zinc anode, thereby greatly enhancing the stability of zinc in acidic media.
[0087] Effect example 2:
[0088] The zinc negative electrode in the zinc ion battery of Example 3 was subjected to XRD diffraction pattern analysis, and the surface and cross section of the zinc negative electrode were analyzed by electron microscope to obtain Figure 3 and Figure 4 , Figure 3 is the XRD diffraction spectrum of the zinc negative electrode of the zinc ion battery of Example 3 of the present application, Figure 4 It is a characterization diagram of the zinc negative electrode of the zinc ion battery of Example 3 of the present application, wherein e is a surface SEM image of the zinc negative electrode, and f is a cross-sectional SEM image of the zinc negative electrode.
[0089] like Figure 3 As shown, after analysis and comparison, in addition to the Zn peak matching PDF No. 01-1238, the diffraction spectrum also includes the CuZn5 peak matching PDF No. 35-1151 and the In peak matching PDF No. 01-1042; therefore, it can be seen that a bimetallic active site In-CuZn5 is formed on the zinc negative electrode.
[0090] like Figure 4 As shown in Figure e, the surface of the zinc anode is uniformly distributed with granular bimetallic active sites. Figure 4 As shown in Figure f, the bimetallic active sites on the surface of the zinc negative electrode form a layered structure, which can provide abundant nucleation sites, thereby promoting the efficient deposition of Zn and effectively inhibiting the hydrogen evolution reaction, thereby improving the stability of the zinc anode in an acidic environment.
[0091] Effect Example 3: Electrochemical Performance Analysis
[0092] The zinc anode (In-Cu@Zn) and bare zinc (Bare Zn) of the zinc ion battery of Example 3 were taken for electrochemical performance analysis. The specific experimental contents include:
[0093] (1) A platinum sheet was used as the auxiliary electrode, Ag / AgCl was used as the reference electrode, In-Cu@Zn and Bare Zn were used as the working electrodes, and a solution containing ZnSO4 and SnCl4 (pH 1.2) was used as the electrolyte to form a three-electrode system. The scan rate was 1 mV / s and the voltage range was -1.1 to 0.85 V. The Tafel curves of In-Cu@Zn and Bare Zn were measured.
[0094] (2) With platinum as the auxiliary electrode, Ag / AgCl as the reference electrode, In-Cu@Zn and Bare Zn as the working electrodes, respectively, and Na2SO4 solution (pH 1.2) as the electrolyte, a three-electrode system was formed with a scan rate of 1 mV / s and a voltage range of -1.1 to -1.8 V. The linear sweep voltammetric curves of In-Cu@Zn and Bare Zn were measured.
[0095] (3) The Gibbs free energy of the bimetallic active sites In-CuZn5 and Zn(101) on the surface of the zinc anode of the zinc ion battery of Example 3 during the kinetic process of hydrogen evolution reaction was measured respectively.
[0096] Based on the above experiments, Figure 5 , Figure 6 and Figure 7 , Figure 5 is the Tafel plot of In-Cu@Zn and Bare Zn, Figure 6 is the linear sweep voltammetry curve of In-Cu@Zn and Bare Zn, Figure 7 This is the HER Gibbs free energy data diagram of In-CuZn5 and Zn(101).
[0097] like Figure 5 As shown in the figure, the corrosion behavior of In-Cu@Zn was evaluated using the Tafel polarization curve test with bare zinc as the control. The corrosion potential of In-Cu@Zn was -0.956 V (compared with Ag / AgCl), which was much higher than that of bare zinc (-0.983 V), indicating that it has stronger corrosion resistance under acidic conditions.
[0098] Generally, the corrosion rate of Zn in acidic environments is influenced by the kinetics of the hydrogen evolution reaction (HER). Figure 6 The LSV curves of bare zinc (Bare Zn) and In-Cu@Zn in 1M pure Na2SO4 electrolyte (pH 1.2) are shown. It is worth noting that the In-Cu@Zn electrode exhibits a lower hydrogen evolution current density in the voltage range of 1.1-1.8V. Compared with bare zinc, the starting potential of the HER of In-Cu@Zn (-1.64V, relative to Ag / AgCl) is significantly negatively shifted (-1.48V), which confirms that In-CuZn5 has the ability to alleviate the hydrogen evolution reaction of the zinc electrode.
[0099] Gibbs free energy (ΔG) is a key parameter for evaluating the activity of hydrogen evolution reaction (HER). For further study, we used DFT calculations to compare the change in Gibbs free energy of H adsorption (ΔGH*) between In-CuZn5 and bare Zn. Figure 7 As shown. The ΔGH* of bare zinc is about 0.22 eV, close to the thermoneutral state, indicating that HER is more likely to occur on the zinc surface. In contrast, the ΔGH* of In-CuZn5 is significantly higher at 0.68 eV, indicating that the tendency to generate H2 on the surface of In-CuZn5 is much lower. This calculated result is in good agreement with the improvement in corrosion potential and HER overpotential observed in In-Cu@Zn.
[0100] From the above experiments, it can be seen that the bimetallic active site In-CuZn5 formed on the zinc anode of the battery in Example 3 can significantly inhibit the HER reaction of the zinc electrode, improve the corrosion resistance and stability of the zinc electrode in acidic media, and thus help to improve the cycle performance and capacity stability of the zinc ion battery.
[0101] Effect example 4: Charge and discharge performance analysis
[0102] The long-cycle charge and discharge performance of zinc / zinc symmetric batteries using different electrolytes was studied under high current density and equal capacity conditions.
[0103] The specific electrolytes tested include: the electrolyte of Example 1 (In-Cu); the electrolyte of Example 2 (In-Cu-Sn); an aqueous electrolyte (BE) comprising 2M ZnSO4 and 0.2M MnSO4; an aqueous electrolyte (In) comprising 50mM InCl3, 2M ZnSO4 and 0.2M MnSO4; an aqueous electrolyte (Cu) comprising 50mM CuCl2, 2M ZnSO4 and 0.2M MnSO4; an aqueous electrolyte (Sn) comprising 50mMSnCl4, 2M ZnSO4 and 0.2M MnSO4.
[0104] The specific test current density and capacity conditions include: 10mA / cm 2 -5 mAh / cm 2 and 10mA / cm 2 -10 mAhcm 2 .
[0105] Based on the above tests, we get Figure 8 and Fig. 9 , Figure 8 The zinc / zinc symmetrical battery with different electrolytes in Example 4 of the present application is 2 -5 mAh / cm 2The charge and discharge performance data diagram below: Fig. 9 The zinc / zinc symmetrical battery using different electrolytes in Example 4 of the present application is 2 -10 mAh cm 2 The charge and discharge performance data diagram below.
[0106] like Figure 8 As shown, the zinc / zinc symmetric battery using the electrolyte (In-Cu-Sn) of Example 2 is at 10 mA / cm 2 -The amazing cycle life of up to 2250 hours is achieved under high current density conditions, far exceeding other electrolytes. The reasons are: On the one hand, Cu 2+ andIn 2+ It can form bimetallic active sites In-CuZn5 on the surface of zinc anode, providing abundant nucleation sites, thereby promoting the efficient deposition of Zn and effectively inhibiting the hydrogen evolution reaction, thereby improving the stability of zinc anode in acidic environment; on the other hand, Sn 4+ It can hydrolyze in situ to generate SnO2 and HCl, establishing a self-sustaining acidic environment that is crucial for aqueous zinc-ion batteries without the need for additional acidic media. SnO2 is highly acid-resistant and can greatly enhance the stability of zinc in acidic media.
[0107] In addition, the zinc / zinc symmetric battery using the electrolyte (In-Cu) of Example 1 was 2 - achieved a cycle life of 1600 hours under a high current density environment, while the zinc / zinc symmetric battery using the electrolyte (In) only achieved a cycle life of 800 hours, and the zinc / zinc symmetric battery using the electrolyte (Cu) only achieved a cycle life of 100 hours; it can be seen that the electrolyte of the present application contains In 3+ and Cu 2+ They have a synergistic effect and work together to form the bimetallic active site In-CuZn5, neither of which can be missing.
[0108] In addition, the zinc / zinc symmetric battery using the electrolyte (In-Cu) of Example 1 was 2 - achieved a cycle life of 1600 hours under a high current density environment, while the zinc / zinc symmetrical battery using the electrolyte (Sn) only achieved a cycle life of 300 hours, both of which are much lower than the electrolyte (In-Cu-Sn) of Example 2; it can be seen that the electrolyte of the present application has In 3+ , Cu 2+ and Sn 4+ Has a synergistic effect.
[0109] Please continue reading Fig. 9 , at 10mA / cm 2 -10 mAh cm 2Under the conditions, the zinc / zinc symmetric battery using the electrolyte (In-Cu) of Example 1 can still maintain 85.5% of the initial capacity after 1000 hours of cycling, while the cycle life of the zinc / zinc symmetric battery using the conventional electrolyte BE is less than 100 hours. It can be seen that the electrolyte of Example 2 can significantly improve the cycle life and capacity stability of the zinc ion battery.
[0110] Effect Example 5: Cycle Performance Analysis
[0111] At 1mA / cm 2 The cycle performance of the batteries of Example 4 and Comparative Example 1 was tested under the conditions of Fig.10 , Fig.10 This is a graph of the cycle performance test data of Effect Example 5 of the present application.
[0112] like Fig.10 As shown, the battery of Example 4 is at 1 mA / cm 2 After 200 cycles under the conditions of , 84.9% of the initial capacity was still maintained; while the battery of comparative example 1 only maintained 35.8% of the initial capacity under the same conditions.
[0113] It can be seen from the above data that the electrolyte of the present application can significantly improve the cycle life and capacity stability of the battery.
[0114] It is obvious to those skilled in the art that the present application is not limited to the details of the exemplary embodiments described above, and that the present application can be implemented in other specific forms without departing from the spirit or essential features of the present application. Therefore, from any point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present application is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present application. Any figure mark in the claims should not be regarded as limiting the claim involved.
[0115] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. An electrolyte containing multiple cations, characterized in that: The invention comprises a solvent and an electrolyte, wherein the electrolyte comprises a zinc salt, a manganese salt, a copper salt and an indium salt.
2. The electrolyte according to claim 1, characterized in that The molar concentration of the zinc salt is 1.8 to 2.2 mol / L, and the molar concentration of the manganese salt is 0.18 to 0.22 mol / L; and / or, The zinc salt is ZnSO4, and the manganese salt is MnSO4.
3. The electrolyte according to claim 1, characterized in that The molar concentration of the copper salt is 45 to 55 mmol / L, and the molar concentration of the indium salt is 45 to 55 mmol / L; and / or, The copper salt is CuCl2, and the indium salt is InCl3.
4. The electrolyte according to claim 1, characterized in that The electrolyte also includes a tin salt.
5. The electrolyte according to claim 4, characterized in that The molar concentration of the tin salt is 45 to 55 mmol / L; and / or, The tin salt is SnCl4.
6. The electrolyte according to claim 1, characterized in that The solvent is water.
7. Use of the electrolyte according to any one of claims 1 to 6 in the preparation of an aqueous zinc ion battery.
8. An aqueous zinc ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator and the electrolyte according to any one of claims 1 to 6.
9. The aqueous zinc ion battery according to claim 8, characterized in that: The positive electrode is a manganese dioxide positive electrode, and the negative electrode is a metal zinc negative electrode; and / or, The separator is a glass fiber membrane or a cellulose membrane.
10. A method for preparing an aqueous zinc ion battery, characterized in that: include: Dissolve KMnO4 and fully react with MnSO4, collect the precipitate, wash and dry it to obtain MnO2 positive electrode material; After mixing the MnO2 positive electrode material, the conductive additive and polyvinylidene fluoride, N-methylpyrrolidone is added and stirred to obtain a positive electrode slurry; The positive electrode slurry is coated on the hydrophilic carbon paper, and the loading amount of the MnO2 positive electrode material is 1.5-3 mg / cm 2 , after drying, a manganese dioxide positive electrode is obtained; The manganese dioxide positive electrode, the metal zinc negative electrode, the separator and the electrolyte according to any one of claims 1 to 6 are assembled to obtain an aqueous zinc ion battery.
Citation Information
Patent Citations
Water-based zinc-manganese single flow battery
CN105336971A
Lithium zinc manganese water system secondary battery and preparation method thereof
CN107346815A
Aqueous zinc ion battery
CN108807910A
Rechargeable aqueous zinc-manganese battery and assembling method thereof
CN114300669A
Zinc negative electrode, battery and electrode base layer
JP2014149993A
Cited By
Preparation method and application of wide-temperature-water-series zinc ion battery electrolyte
CN120165069A